Pole solutions for flame front propagation - Kupervasser, Oleg; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This ebook deals with solving mathematically the unsteady flame propagation equations. New original mathematical methods for solving complex non-linear equations and investigating their properties are presented. Pole solutions for flame front propagation are developed. Premixed flames and filtration combustion have remarkable properties: the complex nonlinear integro-differential equations for these problems have exact analytical solutions described by the motion of poles in a complex plane. Instead of complex equations, a finite set of ordinary differential equations is applied. These solutions help to investigate analytically and numerically properties of the flame front propagation equations.
Introduction -- Pole-Dynamics in Unstable Front Propagation: The Case of the Channel Geometry -- Using of Pole Dynamics for Stability Analysis of Premixed Flame Fronts: Dynamical Systems Approach in the Complex Plane -- Dynamics and Wrinkling of Radially Propagating Fronts Inferred from Scaling Laws in Channel Geometries -- Laplacian Growth Without Surface Tension in Filtration Combustion: Analytical Pole Solution -- Summary.
Electronic reproduction.
Keywords: Nonlinear integral equations; Differential equations, Nonlinear; Combustion -- Mathematical models; Electronic books